Programmable Zwitterionic Droplets as Biomolecular Sorters and Model of Membraneless Organelles. Issue 4 (19th November 2021) - Capasso Palmiero, Umberto; Paganini, Carolina; Kopp, Marie R. G.; Linsenmeier, Miriam; Küffner, Andreas M.; Arosio, Paolo
Abstract: Increasing evidence indicates that cells can regulate biochemical functions in time and space by generating membraneless compartments with well‐defined mesoscopic properties. One important mechanism underlying this control is simple coacervation driven by associative disordered proteins that encode multivalent interactions. Inspired by these observations, programmable droplets based on simple coacervation of responsive synthetic polymers that mimic the "stickers‐and‐spacers" architecture of biological disordered proteins are developed. Zwitterionic polymers that undergo an enthalpy‐driven liquid–liquid phase separation process and form liquid droplets that remarkably exclude most molecules are developed. Starting from this reference material, different functional groups in the zwitterionic polymer are progressively added to encode an increasing number of different intermolecular interactions. This strategy allowed the multiple emerging properties of the droplets to be controlled independently, such as stimulus‐responsiveness, polarity, selective uptake of client molecules, fusion times, and miscibility. By exploiting this high programmability, a model of cellular compartmentalization is reproduced and droplets capable of confining different molecules in space without physical barriers are generated. Moreover, these biomolecular sorters are demonstrated to be able to localize, separate, and enable the detection of target molecules even within complex mixtures, opening attractive applications in bioseparation, and diagnostics. Abstract : A strategy to produce programmable liquid droplets via liquid–liquid phase separation of associative synthetic polymers is presented. Starting from zwitterionic polymers as reference, different functional groups able to encode multiple intermolecular interactions are introduced in the polymer. In this way, it is possible to simultaneously control multiple mesoscopic properties of the droplets, opening attractive applications in bioseparation and diagnostics.